The relationship between mindfulness and suboptimal health status: a chain/serial mediation model - Liang, Jingyue; Zhang, Xiaoshuo; Wang, Yuzheng (Frontiers in Psychology, 2024)
Background Suboptimal health status (SHS) represents a third state between health and disease and often progresses into chronic conditions, negatively impacting an individual’s well-being. Studies have shown that mindfulness has a beneficial effect on various SHS symptoms. This study aims to explore the influence of mindfulness on SHS and its underlying mechanisms, with a particular focus on examining the mediating roles of stress and social support. Methods A total of 173 healthy Chinese college or graduate students, with an average age of 21.85 years, participated in this study. Measurements were taken using the Five Factor Mindfulness Questionnaire, the Sub-Health Measurement Scale, the Perceived Stress Scale, and a self-constructed scale that included demographic information. The PROCESS plugin for SPSS was used to assess mediating effects. Results Significant correlations were found among SHS, social support, mindfulness, and perceived stress (|r| = 0.38–0.85, p < 0.01). Specifically, mindfulness showed a significant positive correlation with SHS and social support (r = 0.38–0.77), while perceived stress was significantly negatively correlated with mindfulness, social support, and SHS (|r| = 0.45–0.85). Perceived social support was positively associated with SHS (r = 0.65). Furthermore, social support and perceived stress partially mediated the influence of mindfulness on SHS. Additionally, a sequential mediation effect of perceived social support and stress in the relationship between mindfulness and SHS was supported. Conclusion The cultivation of trait mindfulness may be advantageous for individuals’ sub-health. Perceived social support and perceived stress are important underlying mechanisms contributing to this effect.